Rozwój społeczno-gospodarczy a ochrona środowiska - Ginsbert-Gebert, Adam (Wydział Prawa i Administracji UAM, 1984)
The socio-economic development, in particular rapidly expending processes of industrialization or urbanization of specific countries or regions effect a serious disequilibrium ruling mechanisms of Nature. The said development is a reason of increasing threat or even of environmental degradation, but at the same time it magnifies potentials of environmental protection. Total expenditures on environment shaping and protection in Poland in 1982 reach 4% of global investments in the whole Polish economy. It is estimated that approximately 6% is needed in order to have the needs fulfilled. Poland is undergoing presently not only the economic and social crisis but also the ecological one. The socio-economic development, when properly understood, cannot be carried out at costs of environmental degradation. Generally speaking, the influence of tasks of protection of environment on the socio-economic development has a two fold meaning: — in the short run,, the necessity of intensified protection of environment can result in decrease of that development, — in the long run, resulted effects in environmental protection can contribute to the icrease of development rate. The protection of environment is a set of goals which must be properly accoounted for in plans and programs of a socio-economic development of the state in the interest of the present and future generations. The adopted solutions have to form the environment to reconcile laws of Nature and laws of socio-economic development.
Socio-economic developement and protection of environment